Editorial: Methodology in judgment and decision making research - Andreas Glockner; Benjamin E. Hilbig (Judgment and Decision Making, 2011)
In this introduction to the special issue on methodology, we provide background on its original motivation and a systematic overview of the contributions. The latter are discussed with correspondence to the phase of the scientific process they (most strongly) refer to: Theory construction, design, data analysis, and cumulative development of scientific knowledge. Several contributions propose novel measurement techniques and paradigms that will allow for new insights and can thus avail researchers in JDM and beyond. Another set of contributions centers around how models can best be tested and/or compared. Especially when viewed in combination, the papers on this topic spell out vital necessities for model comparisons and provide approaches that solve noteworthy problems prior work has been faced with.